Factors Inhibiting Persuasive Communication of Agricultural Extension Workers Through Internet Media in Accelerating Information Dissemination in Farmer Women Groups in Ponorogo Regency, Indonesia (International Journal of Religion, 2024)
The development of digital information technology today allows the use of various media for agricultural extension. The internet has become an important medium in disseminating information, including for agricultural extension workers and farmer women groups. Agricultural extension workers have a crucial role in conveying information persuasively and are expected to utilize internet media to support their tasks and accelerate the dissemination of information to farmers. This study examines the obstacles in persuasive communication carried out by agricultural extension workers using internet media to accelerate the dissemination of information to Farmer Women Groups in Ponorogo Regency. The method used is qualitative descriptive with data analysis through in-depth interviews and participatory observation. The informants in this study consisted of agricultural extension workers and members of farmer women groups in Babadan District. The results of the study showed that there were technical obstacles such as lack of technological facilities and uneven internet access, as well as time limitations due to the dual roles of group members. Low digital literacy is also an obstacle, influenced by age, low education, and lack of technological experience. Behavioral barriers include a preference for in-person counseling and age stereotypes, where older members lack confidence in using technology. The influence of the social environment also plays a role. The suggested solutions include increasing digital literacy, improving technological infrastructure, and handling stereotypes and negative social influences to increase the effectiveness of counseling.